PROSEDUR PENINDAKAN PELANGGAR LALU LINTAS DI JALAN RAYA DIKAITKAN DENGAN PENEGAKAN HUKUM DALAM UNDANG-UNDANG NOMOR 22 TAHUN 2009 TENTANG LALU LINTAS DAN ANGKUTAN JALAN DALAM RANGKA PERLINDUNGAN HAK ASASI WARGA NEGARA - Martinus Zebua; Erdianto Effendi; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
The road is any track in any form that is ope road is any track in any formthat is open to public traffic, so the authorities have to create the rules andprocedures for traffic to be orderly, safe and smooth namely Law Number 22 Year2009 regarding Traffic and Road Transportation conducted by special policetraffic , However, in practice, the traffic police who investigate traffic inspectionat instigating violence and verbal abuse against the driver and the road, so thatthe rights of citizens neglected road users. The purpose of this thesis, namely:First, To know Offenders Traffic Enforcement Procedure On Highway. Secondly,To find the settings in traffic enforcement procedure if it has been providingprotection against the Rights of Citizens.This type of research can be classified into types of normative juridicalresearch, because in this study the authors conducted a study of the legislation onthe subject under study. In this study the source of the data used primary data,secondary data, and the data tertiary data collection techniques in this research isthe study of literature. From this research, there are two main things that can beinferred. First, the prosecution traffic violators on the highway associated withthe enforcement of Law Number. 22 Year 2009 regarding Traffic and RoadTransportation still has not done well and efficiently, because many members ofthe traffic police to raid without a letter of assignment from superiors police ,because influenced economic factors resulting in the illegal harvesting of thedriver of road users. Second, the prosecution of traffic offenders carried out bythe Police Traffic many violations of Human Rights and still provide protection.Due to a lack of supervision, training and coaching.Suggestions writer, first, that it is necessary the police chief in the field oftraffic should be routine monitoring and close supervision to members and as wellas the provision of strict sanctions against traffic police officers abuse theirauthority in carrying out the task. Second, that it is necessary the police chief togive guidance and education of the police more leverage against traffic.Keywords : Traffic Violator Prosecution Procedure And Citizens' RightsProtection Road Users.